Stroke Laterality Did Not Modify Outcomes in the HERMES Meta-Analysis of Individual Patient Data of 7 Trials. Issue 8 (August 2019) - Almekhlafi, Mohammed A.; Hill, Michael D.; Roos, Yvo M.; Campbell, Bruce C.V.; Muir, Keith W.; Demchuk, Andrew M.; Bracard, Serge; Gomis, Meritxell; Guillemin, Francis; Jovin, Tudor G.; Menon, Bijoy K.; Mitchell, Peter; et al.
Abstract : Background and Purpose—: There is contradictory evidence on the impact of the stroke side (hemisphere) on outcomes. We investigated any effect modification by laterality on stroke patients' outcomes in recent endovascular trials. Methods—: Individual patient-level data were combined in this meta-analysis of all patients included in randomized trials comparing endovascular thrombectomy predominantly done with stent retrievers with standard care in anterior circulation ischemic patients with stroke (HERMES [Highly Effective Reperfusion Using Multiple Endovascular Devices] Collaboration). We stratified the 90-day functional outcome assessed by ordinal analysis of the modified Rankin Scale according to the stroke side of patients treated with endovascular therapy versus standard care, adjusted for important prognostic variables. Results—: The meta-analysis included 1737 patients (871 right hemispheric strokes and 866 left hemispheric) from 7 trials. Baseline median National Institutes of Health Stroke Scale scores were significantly higher in left (20) versus right (16) hemispheric strokes ( P <0.001). Other clinical and radiological baseline characteristics were similar. The beneficial response to endovascular therapy assessed by 90-day modified Rankin Scale shift was not modified by the side of the stroke. There were no significant differences between right and left hemispheric stroke in the 90-day functional outcome (modified Rankin Scale score ⩽2; 40.7% [95% CI, 37.4%–44.1%] versus 37.6% [95% CI, 37.4%–44.1%]; P =0.19), median final infarct volumes (45 versus 39.5 mL, P =0.51), nor 90-day mortality (15.1% vs 16.8%, P =0.31). Conclusions—: Stroke side was not a prognostic factor and did not modify the treatment effect among patients treated in the endovascular or control groups in recent endovascular thrombectomy trials. Abstract : Supplemental Digital Content is available in the text.